2013
DOI: 10.1021/ja401434x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Tandem and Triple-Junction Polymer Solar Cells

Abstract: We demonstrate tandem and triple-junction polymer solar cells with power conversion efficiencies of 8.9% and 9.6% that use a newly designed, high molecular weight, small band gap semiconducting polymer and a matching wide band gap polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
458
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(462 citation statements)
references
References 27 publications
3
458
1
Order By: Relevance
“…Design, synthesis and applications of novel conjugated polymers for polymer solar cells (PSCs) have received substantial attention over the past decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Significant improvements have been achieved in understanding the correlations between polymer structure and photovoltaic performance, which have helped to boost the power conversion efficiency (PCE) over 7% in several well-known backbones, such as benzodithiophene (BDT) and thienothiophene (TT) (PBDT-TT) [15][16][17][18][19][20][21][22][23][24][25][26][27][28], BDT and benzothiadiazole (BT) (PBDT-BT) [29,30], BDT and thienopyrroledione (TPD) (PBDT-TPD) [31], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Design, synthesis and applications of novel conjugated polymers for polymer solar cells (PSCs) have received substantial attention over the past decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Significant improvements have been achieved in understanding the correlations between polymer structure and photovoltaic performance, which have helped to boost the power conversion efficiency (PCE) over 7% in several well-known backbones, such as benzodithiophene (BDT) and thienothiophene (TT) (PBDT-TT) [15][16][17][18][19][20][21][22][23][24][25][26][27][28], BDT and benzothiadiazole (BT) (PBDT-BT) [29,30], BDT and thienopyrroledione (TPD) (PBDT-TPD) [31], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion to chalcogenide films is attained by thermal ion exchange exposing the precursor metal oxide film to the chalcogen gas flux at high temperature (for the details, see [10]). We applied it to the deposition of PbTe films from a lead based compound plumbonacrite (Pb 10 (CO 3 ) 6 O(OH) 6 ) deposited at first stage by CBD under UV illumination (actually, it is Photo Chemical Bath Deposition, or PCBD). At the second stage, Te hot gas was used as the chalcogen source in CVD reactor.…”
Section: Techniques Of Formation Of Semiconductor Layersmentioning
confidence: 99%
“…This is realized in multi-layers (multi junction, or tandem) solar energy converters, see [1]- [4], that have efficiency of 30-40%, with a recent record of 44.7% [4]. It must be noted that tandem construction is a widely accepted way of design of different efficient solar energy converters, like thin film Si-based cells [5] or polymer ones [6].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In a few occasions it has been shown that with the use of tandem or triple junction devices one may overcome the efficiency of the optimal single junction device, 23,24 setting the PCE for organic tandem cells at above 10 %. 24 Tandem solar cells design and fabrication is, however, a demanding task due to the requirement of a suitable interconnection layer (ICL) for charge recombination.…”
Section: Introductionmentioning
confidence: 99%